Mali : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance Report discusses key recommendations for implementing fiscal decentralization in Mali. It proposes to set an optimal administrative organization of the territory, which should aim at building consistent and sustainable local governments that are best suited to address specific local needs. In this context, the regions deemed to be best suited to handle funds are envisaged to be decentralized and with large-scale development actions. The local government revenue should be optimized through local taxation, and an efficient system of transfers from the central government should be introduced. The report also proposes establishing good financial governance in Mali.